Foreign direct investment through privatisation of state-owned enterprises : a comparative analysis of South Africa and Zambia - Masindi, Ntungufhadzeni Austin (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2000.